Foreign Aid in China - Zhou, Hong (Springer, 2015)
Foreign aid has connected China and the international community through many channels, and created new types of strong partnerships throughout the world. As a recipient country, China and donors have engaged in an unprecedentedly deep level of cooperation on development-related issues. China’s development experience has resulted in key changes to the relationships and partnerships between China and donors, from receiving foreign aid to entering into development cooperation. China has provided valuable experiences for other developing countries, experiences that are all the more relevant because they have revealed key factors at work in developing recipient countries. This has also led China to form closer cooperative relationships with other developing countries with regard to development issues. In short, foreign aid has changed China.